Serum branched chain amino acids: an effective indicator of diabetic kidney disease - Liu, Min; Yang, Yanhui; Liu, Yajin; Peng, Xiaoyue; Hou, Yi; Zhang, Xuejiao; Sun, Haipeng; Shan, Chunyan (Frontiers in Endocrinology, 2023)
Introduction: In recent years, there has been a growing association between elevated circulating levels of branched-chain amino acids (BCAA) and diabetes mellitus. However, the relationship between serum BCAA levels and diabetic kidney disease (DKD) remains ambiguous. This study aims to investigate serum BCAA levels in DKD patients at various stages and assess the correlation between BCAA and clinical characteristics. Materials and Methods: We enrolled patients with type 2 diabetes mellitus (T2DM) who were admitted to our hospital and categorized them into three groups based on different DKD stages: normal proteinuria, microproteinuria, and macroalbuminuria groups. Forty healthy volunteers were included as the control group, and we measured serum BCAA concentrations using liquid chromatography-mass spectrometry (LC-MS). Subsequently, we conducted correlation and regression analyses to assess the associations between BCAA and clinical indicators. Results: Serum BCAA levels were significantly elevated in T2DM patients compared to healthy controls. However, these levels exhibited a gradual decline with the progression of DKD. Furthermore, after adjusting for age, gender, and disease duration, revealed that serum albumin, urinary transferrin, and urinary microalbumin remained independently associated with BCAA. Discussion: Our findings suggest a noteworthy decline in serum BCAA levels alongside the advancement of DKD. Additionally, serum BCAA exhibits an independent correlation with renal function indicators. These observations point to the possibility that serum BCAA concentrations in individuals with T2DM hold promise as a crucial predictor for both the initiation and progression of DKD.